Building bridges: Bilateral manager connections and international trade - Felix Hoch; Jonas Rudsinske (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2021)
We investigate whether top managers with personal ties to a foreign country facilitate trade with that country by overcoming bilateral trade barriers that obstruct international business relationships. Using individual managers' nationality, we construct a novel database of bilateral top manager connections. We analyze the trade effects of these bilateral manager connections both on the firm and on the country level. On the country level, we provide evidence for a positive effect on both bilateral exports and imports. On the firm level, we find positive effects on destination-specific foreign sales. We show that this firm-level effect is especially pronounced for institutionally distant destinations, which we interpret as bridging the gap between institutionally dissimilar countries. Furthermore, the effect is stronger for destinations with less developed institutions indicating that manager connections help overcoming trade barriers created by low institutional quality. Moreover, we show that the strength of this effect also depends on characteristics of the individual manager. Namely, the effect differs between connections of male and female managers. Gender discriminating institutions in the destination country severely downsize the pro-trade effect of female managers' connections, which could give rise to an unintended importing of gender inequality regarding management positions.
Keywords: F14; F22; F23; J16; J61; K38; M16; 330; International trade; gravity; international business; board composition; institutions; gender equality